Gene editing and gene-based therapeutics for cardiomyopathies - Ohiri, Joyce C (Heart Fail Clin, 2018)
With an increasing understanding of genetic defects leading to cardiomyopathy, focus is shifting to methods for correcting these underlying genetic defects. One approach involves treating mutant RNA through antisense oligonucleotides, and the first drug has now received regulatory approval to treat specific mutations associated with Duchenne muscular dystrophy. In contrast, gene editing targets DNA, and is currently being evaluated in the preclinical setting. For inherited cardiomyopathies, especially those that are caused by autosomal dominant mutations, genetic correction strategies require tight specificity for the mutant allele. Gene editing methods are currently in testing to create deletions that may be useful to restore protein expression by bypassing mutations and restoring protein production. Site specific gene editing is a less efficient process than inducing deletions. In both cases, it is essential to target the mutant allele while avoiding the non-mutant allele. Antisense oligonucleotide drugs have limited access to tissues, including the heart. Importantly, it is necessary to provide continual dosing with antisense oligonucleotides as their effect is temporary. For DNA-mediated gene editing, current research approaches rely on viral delivery of nucleases and guide RNAs to the heart. In principle, gene editing requires a one-time treatment as a permanent genetic correction. Gene editing targeting the germline is associated with ethical dilemmas.